Phylogenetic Relationships of Ornamental Chaetodontidae in The South Coastal of West Java, Indonesia - Ihya, Silma Safira; Nuryanto, Agus; Prabowo, Romanus Edy; Bhagawati, Dian; Kusbiyanto, Kusbiyanto (Jurnal Biodjati, 2020)
Marine ornamental trade has been developingÂ for several yearsÂ withÂ Indonesia asÂ one of the major exporterÂ countries. Among the popular marine ornamental fish in the local and international markets belong to the family of Chaetodontidae.Â The existence of this family has beenÂ reported from several areas in Indonesia. However, no information isÂ availableÂ in terms of their phylogenetic relationships of the fishÂ from theÂ south coast of West Java. The aimÂ of this research wasÂ to assesÂ the phylogenetic relationships among ornamental fish members of Chaetodontidae in the South Coast ofÂ WestÂ Java.Â Fish samples were collected from two trading sites Ujung GentengÂ and Taman Manalusu. Collected fishÂ were identified using a previously published study.Â The evolutionary relationships among species wereÂ analyzed statistically through phylogenetic analysis based on maximum parsimony algorithm and Kimura 2- Parameter substitution model as implemented in PAUP 4.0 software. Tree branching pattern supported by 1000 bootstraps pseudo-replicates and out-group comparison.Â Daschyllus trimaculatusÂ used as outgroup species.Â Based on the study, Chaetodontidae fromÂ the South Coast of West Java formedÂ one monophyletic group compared to Dascylus trimaculatus with Chelmon rostratus wasÂ the basal species. All the remaining species wereÂ the derived species. There are CI and RI value gained. The consistency index (CI) value of this family is 0.5833, and the retention index (RI) is 0.5082.Â